Barriers to the Use of Psychosocial Support Services Among Adolescent and Young Adult Survivors of Pediatric Cancer - Gardner, Molly H. (Mary Ann Liebert, Inc., 2014)
Purpose: Adolescent and young adult (AYA) survivors of pediatric cancer commonly report both functional and emotional difficulties, yet many of their mental health needs are not met. Given the unique needs of these survivors, this study examined barriers to psychosocial support service utilization in this population, including accessibility, personal preferences, and practical barriers such as insurance and transportation. Methods: Thirty-six adolescent and young adult survivors of pediatric cancer (aged 15–29) with mental health difficulties (i.e., anxiety or depression) completed surveys assessing access and utilization of services and barriers to utilization. Services assessed included the use of mental health professionals, a pastor or someone in a place of worship, and support groups. Results: Half of the participants utilized a mental health professional, but other forms of support were used less frequently. Utilization of services was related to insurance status and use of prescription medication. Greater time since completion of treatment was a barrier to utilizing psychosocial support services. Conclusion: Use of psychosocial support services is linked closely with use of other healthcare services, including taking prescription medication for mood difficulties. Results have implications for how primary care and oncology providers address barriers to these services among AYA survivors of pediatric cancer.